2001
DOI: 10.1046/j.0022-202x.2001.01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Light Downregulates CD95 Ligand and Trail Receptor Expression Facilitating Actinic Keratosis and Squamous Cell Carcinoma Formation

Abstract: Long-term ultraviolet light exposure of human skin epidermis in Caucasians is associated with an increased risk for the development of melanoma and nonmelanoma skin cancers. Ultraviolet radiation not only induces DNA damage in epidermal cells, it also interferes with skin homeostasis, which is maintained by a unique distribution pattern of apoptosis-inducing and apoptosis-preventing molecules. We demonstrate that, beside CD95 ligand, TRAIL and TRAIL receptors also function as important sensors in the human epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 37 publications
10
78
0
Order By: Relevance
“…The loss of CD95 expression in BCCs was previously reported, 20 and our results confirm that observation. On the basis of our observations in chronically sun-exposed skin, and the data obtained from controlled UV light exposure of human skin in volunteers, 19 we found that changes in Fas expression follow a hyperbolic pattern. With initial actinic damage, Fas expression is up-regulated and is associated with apoptosis of sun-exposed keratinocytes.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The loss of CD95 expression in BCCs was previously reported, 20 and our results confirm that observation. On the basis of our observations in chronically sun-exposed skin, and the data obtained from controlled UV light exposure of human skin in volunteers, 19 we found that changes in Fas expression follow a hyperbolic pattern. With initial actinic damage, Fas expression is up-regulated and is associated with apoptosis of sun-exposed keratinocytes.…”
Section: Discussionsupporting
confidence: 51%
“…Chronic exposure to sunlight (as evidenced by the presence of solar elastosis), up-regulates Fas expression, which extends up to the granular layer, similar to the experimental data. 12,18,19 With further sun-induced skin damage resulting in AK, which represents the earliest morphologic stage in development of skin carcinoma, there was marked down-regulation, or total loss of CD95 expression. This down-regulation was retained in invasive SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin sections of the lymph node tissue were immunohistochemically stained for the following antigens: CD4 (Novocastra, clone 1F6, dilution 1:20), CD8 (Dako Cytomation Copenhagen Denmark, clone, C8/144B), CD21 (Cell Marque, clone 2G9), p24 (Dako, clone Kal-1,1:4), Bcl-2 (Dako, clone 124), IL-7Ra (Santa Cruz Biotechnologies, 1:100), c-Flip [22] (1:400), Fas (Novocastra, clone GM30; 1:20), FasL [22] (1:80), TRAIL (Santa Cruz Biotechnologies, K-18, 1:75), and active caspase 3 (R&D; 1:1,500). The sections were stained according to the manufacturers' instructions; horse radish peroxidase (HRP)-conjugate (Envision + system, Dako) and AEC substrate (Dako) were used except for the CD4 stains, in which the ABC-Elite-Complex (Vector laboratories Inc, Burlingame, CA, USA) and DAB substrate (Dako) were used.…”
Section: Immunostaining Of the Lymph Node Tissuementioning
confidence: 99%
“…For all other cellular (CD4, interfollicular CD8, CD21) and apoptosis-related antigens (Bcl-2, c-Flip, IL-7Ra, Fas, FasL, active caspase 3), the gray level intensity was determined by computerassisted image analysis using the Openlab program (Improvision, Coventry, UK) as described by Bachmann et al [22].…”
Section: Morphometry and Quantificationmentioning
confidence: 99%
“…Cryosections were made and stained to detect Gli2, Bcl-2 or cFlip. To quantitate their expression, computer-assisted image analysis was performed (Bachmann et al, 2001). The values obtained from the transfected sections were compared with the untransfected (nil) sections, which were set to 100%.…”
Section: Gli2 Gene Silencing In Bcc Tissue Ex Vivo Renders Bcc Cells mentioning
confidence: 99%